Land Use Suitability and Spatial Plan Compliance in Kalianda District, South Lampung - Rasyid, Fachri Muhammad (Program Studi Perencanaan Wilayah dan Kota, UPT Publikasi Publikasi Ilmiah UNISBA, 2026)
This study investigates the alignment between current land use and the official spatial pattern plan (RTRW) of South Lampung Regency, concentrating on Kalianda District, a region characterized by significant economic activity and environmental sensitivity. The study addresses the deficiency in empirical assessments of land use compliance in coastal areas susceptible to land conversion and disaster risks. A Geographic Information System (GIS)-based overlay analysis was applied to compare 2024 satellite-derived land use maps with the RTRW 2011–2031 spatial pattern. The results show that 75.99% (13,301.57 ha) of the district follows the spatial plan, while 24.01% (4,202.65 ha) does not. The biggest difference is that dryland agriculture has been turned into paddy fields, which make up 1,538.17 ha (8.79%). These mismatches are driven by population growth, economic expansion, and limited public awareness of spatial policy. The study contributes to urban and regional planning by demonstrating the need for adaptive RTRW revisions, integrated spatial monitoring systems, and participatory governance to balance development with environmental protection. Findings provide practical input for policy refinement, particularly in aligning spatial plans with dynamic socio-economic and environmental realities.